Constructing a measure of adult attachment styles - Khadidja MEBARKI; Mohamed BOUFATEH; Selami BAHI (Social Sciences Journal, 1970)
The study aimed at building a measure of attachment patterns in adults and verifying itspsychometric properties on a sample of 385 university students from the Faculty ofHumanities and Social Sciences of Ammar Thaliji University in Laghouat. The scale wascharacterized by high cycometric characteristics and proven validity and reliability for theAlgerian environment. And included 80 items in its final form represent four patterns are«safe and avoidance and contradictory and separate», and identified the patterns prevailingin the student community where the safe mode ranked first followed by the pattern of contrastand then avoid and then separated.